The effects of regular physical activity on the quality of life of Alzheimer's patients: An integrative review (Research, Society and Development, 2023)
Alzheimer's disease (AD) is a progressive and irreversible neurodegenerative process that has a direct impact on the quality of life of the elderly and thus reduces their independence and functionality, prompting constant studies to promote strategies to mitigate this condition. Within this context, physical activity has been identified as a possible ally in reducing cognitive decline in people with AD and improving physical capabilities. Therefore, it was decided to present the main contributions of physical activity carried out in a systematic way to the quality of daily life of people with AD. The specific objectives were as follows: 1) to list the effects of ageing on the life of the individual; 2) to present definitions of AD, its signs, symptoms and treatments; and 3) to present the main benefits attributed to the practice of physical activity in improving the quality of life of people with AD; 4) to verify the possibilities of physical activity in the prevention of AD. To this end, we carried out a qualitative, descriptive-exploratory bibliographical study, based on a literature review, in order to find the main results of the most recent research into the benefits of physical activity in the prevention and management of AD. As a result, we found a consensus that the practice of regular physical activity improves cerebral blood circulation, stimulating the release of substances that help the functioning of the central nervous system, with an improvement in cognitive functions in patients with AD, helping both to prevent the disease and to reduce and "manage" the limitations it causes.